Oxford advanced learner's dictionary of current English - Hornby, Albert Sydney; Deuter, Margaret; Turnbull, Joanna; Bradbury, Jennifer (Managing editor); Oxford University Press (Oxford ; New York : Oxford University Press, 2015)
Includes Speaking Tutor. Writing Tutor and Language Banks, offering models, analysis and tips on communicating at work, in exams, or in daily life.
"with new iSpeaker, iWriter on DVD and online"--Cover.
Includes Speaking Tutor. Writing Tutor and Language Banks, offering models, analysis and tips on communicating at work, in exams, or in daily life.
System requirements: Windows 7, Windows 8. Macintosh OSX 10.4 - 10.10
Keywords: English language -- Dictionaries; English language -- New words -- Dictionaries